255 An Audit on the Knowledge of Junior Doctors About DKA at a Local Hospital, Khartoum, Sudan. (28th February 2022) - Elhassan, A.B.E.; Ibrahim, A.; Salman, M.S.T.; Ali, Al.; Mohammed, O.A.A.; Bashir, S.A.T.; Mohamed, N.E.M.; Ali, M.; Abdalla, N.
Abstract: Aim: DKA is the most common cause of death in pediatric patients with insulin-dependent diabetes mellitus (IDDM). Junior doctors have a significant role in the management of those patients. We conducted this audit to assess and improve the knowledge of house officers about the characteristic features and management of DKA. Method: The audit was conducted in Alshuhada hospital, Khartoum. It consisted of two cycles (2019–2021). A 14 items questionnaire based on Sudan Diabetes Mellitus guidelines 2011 was used for the assessment. All house officers in the department of pediatrics were involved in this study. Teaching sessions were used as an intervention in the first cycle, while poster presentations and teaching sessions were used in the second cycle. Results: Nine house officers participated in the first cycle, while seven house officers were involved during the second cycle. The correct choice of initial fluid correction was selected by 55.5%, 88.8%, and 100% of the house officers before the first cycle, after the first cycle, and after the second cycle, respectively. The figures for the initial management of cerebral edema also rose from 33.3% to 66.7% after the first cycle and reached 100% after the second cycle. The percentage of house officers who identified Investigations needed in suspected cases of DKA improved with each cycle, from 66% to 77% in the first cycle and increased to 100% after the second cycle. Conclusions: Teaching sessions and posters helped to improve the knowledge of the House officers about the diagnosis and management of DKA.